Temporal and Spatial Variations of Storm Time Midlatitude Ionospheric Trough Based on Global GNSS‐TEC and Arase Satellite Observations. Issue 15 (14th August 2018) - Shinbori, Atsuki; Otsuka, Yuichi; Tsugawa, Takuya; Nishioka, Michi; Kumamoto, Atsushi; Tsuchiya, Fuminori; Matsuda, Shoya; Kasahara, Yoshiya; Matsuoka, Ayako; Ruohoniemi, J. Michael; Shepherd, Simon G.; Nishitani, Nozomu
Abstract: Temporal and spatial variations of the midlatitude ionospheric trough during a geomagnetic storm on 4 April 2017 have been investigated using Global Navigation Satellite System total electron content data together with Arase satellite observations. After the geomagnetic storm commencement, the trough minimum location moves equatorward from 60 to 48° in geomagnetic latitude within 4 hr. The trough minimum location identified from the Global Navigation Satellite System total electron content data is located near the footprint of an abrupt drop of electron density detected by the Arase High‐Frequency Analyzer instrument. The longitudinal variation of the trough minimum location shows a significant variation with a scale of 1, 000–2, 500 km during both storm and quiet times. This phenomenon has not yet been reported by previous studies. After the onset of the storm recovery phase, the trough minimum location rapidly moves poleward back to the quiet time location within 4 hr. Plain Language Summary: Geomagnetic storms lead to a sever change in the plasma environment in the ionosphere and magnetosphere. Because their storm time disturbances in these regions cause an enhancement of positioning error and satellite anomaly due to the ionospheric electron density variation and magnetospheric high‐energy particles, to clarify the characteristics of storm time variation of plasma environment and its physical mechanism is essential for prediction of the Geospace environmental change as space weather. In this study, we analyzed global positioning system total electron content data and Arase satellite observations in the inner magnetosphere to monitor a storm time change in the shape of the plasmasphere that controls the generation and propagation of plasma waves. Our analysis results show that the location of the midlatitude trough minimum identified from the total electron content data rapidly moves equatorward and poleward within 4 hr during the main and recovery phases. The location of the midlatitude trough minimum almost corresponds to that of the plasmapause detected by the Arase satellite. The longitudinal distribution of the midlatitude trough minimum shows a significant variation with its scale of 1, 000–2, 500 km. This feature is also seen during a geomagnetically quiet time. This phenomenon has not yet been reported by previous works. Key Points: The trough minimum location moves quickly equatorward and poleward during the storm main and recovery phases, respectively The longitudinal distribution of the trough minimum location shows a significant variation with a scale of 1, 000–2, 500 km The trough minimum location is located near the footprint of the plasmapause signature in the inner magnetosphere